Molecular Dynamics Modeling of the Effect of Nanotwins on the Superelasticity of Single-Crystalline NiTi Alloys - Yang Guo; Xiangguo Zeng; Huayan Chen; Tixin Han; Heyi Tian; Fang Wang (Advances in Materials Science and Engineering)
The objective of this work is to simulate the superelasticity and shape-memory effect in a single-crystalline nickel-titanium (NiTi) alloy through a molecular dynamics (MD) study. Cooling and heating processes for this material are reproduced to investigate the temperature-induced phase transformation in its microstructure. It is found that the martensitic transformation and its reverse process occur accompanied by an abrupt volume change, and the transformed variants lead to the appearance of the (001) type compound twin. In addition, the transform temperatures for martensite start (Ms) and austenite finish (Af) are determined, respectively. The results indicate that when the temperature is beyond Af during the compressive loading-unloading, the superelastic behavior becomes pronounced, which is attributed to the role of nanotwins on the transformation from the austenitic phase (B2) to martensitic phase (B19′). Compared to existing experimental data, a reasonable agreement is achieved through the modeling results, highlighting the importance of the compound twins for dominating the superelasticity of nanostructured NiTi alloys.